Reading and not reading The faerie queene - Nicholson, Catherine (Princeton University Press, 2021)
The 400-year story of readers' struggles with a famously unreadable poem - and what they reveal about the history of reading and the future of literary studies.
10.23943/princeton/9780691198989.001.0001
Keywords: Spenser; Edmund; Faerie queene; The faerie queene; Epic poetry; English